Water supply network with zonation system in Golo Wua dan Golo Watu Village, Manggarai District - Teguh Taruna Utama (Sustinere: Journal of Environment and Sustainability, 2020)
Drinking water sources in Manggarai Regency are mostly supplied from springs. Golo Wua and Golo Watu are two villages in Manggarai Regency that utilize springs. About 12.06 liters/second of drinking water is needed by residents in those villages. This study addresses to forecast the demand of drinking water. This study found that pressure values in manual calculations range from 1.85 meters to 84.22 meters. The minimum pressure requirements from BPP-SPAM is 7 meters (0.7 bar). While the simulation results using the EPANET program, the pressure value is at 1.90 meters up to 84.22 meters. Therefore, the pipe diameter selection is appropriate and the pressure meets the requirements of the BPP-SPAM. The difference between pressure values less than 5% indicates that the selection is the right pipe diameter. Choosing the right pipe diameter will optimize the distribution network in the villages of Golo Wua and Golo Watu. The selected pipe is high density polyethylene type. Selected pipe diameter 1Â½"; 2"; 2Â½â€; 3"; 4 and 5". The pipe has a pressure resistance of up to 125 meters.